Assembly Line Planning and Control - Thomopoulos, Nick T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Assembly Line Planning and Control describes the basic fundamentals of assembly lines for single model lines, mixed model make-to-stock lines, mixed model make-to-order lines and for one-station assembly. The book shows how to select the quantity of units to schedule for a shift duration, compute the number of operators needed on a line, set the conveyor speed, coordinate the main line with sub-assembly lines, assign the work elements to the operators on the line, sequence the models down the line, sequence the jobs down the line, calculate the part and component requirements for a line and for each station, determine the replenish needs of the parts and components from the suppliers, compute the similarity between the models being produced and show applications, use learning curves to estimate time and costs of assembly, and measure the efficiency of the line. The material is timeless and the book will never become obsolete. The author presents solutions with easy-to-understand numerical examples that can be applied to real-life applications.
Introduction -- Assembly Systems -- Some Fundamentals -- Preliminary Planning -- Inventory Replenishments -- Single Model Assembly -- Mixed Model Make-to-Stock Assembly -- Mixed Model Make-to-Order Assembly -- Postponement Assembly -- One Station Assembly -- Similarity Index -- Learning Curves.
Keywords: Economics; Structural control (Engineering).; Operations research; Economics/Management Science; Operation Research/Decision Theory; Production/Logistics/Supply Chain Management; Operating Procedures, Materials Treatment